2017
DOI: 10.1080/03007995.2017.1284656
|View full text |Cite
|
Sign up to set email alerts
|

Real-world adherence assessment of lurasidone and other oral atypical antipsychotics among patients with schizophrenia: an administrative claims analysis

Abstract: In Medicaid and commercial populations, patients treated with lurasidone demonstrated greater adherence compared to patients treated with other atypical antipsychotics. Limitations of using administrative claims data include potential errors or inconsistencies in coding, and lack of complete clinical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…When a PDC of 80% or higher was used, adherence was reported to be below 50% (range 9.0-33.2%) in 11 of 12 studies with 6-12 months of follow-up [34,42,[44][45][46][47][48][49][50][51][52] (Table 2). These findings were consistent with adherence rates assessed by MPRs of 80% or higher (Table 2), with oral antipsychotic adherence of less than 50% in 5 of 7 studies over 6-12 months of follow-up [29,45,53,54], and by MPRs of 70% or higher [19,80,81]; for reporting an 18-month time point or only baseline adherence [38,56,77]; for not reporting a time period [76]; and for reporting mean PDC or MPR values only [32,37,65,66] Studies were excluded for reporting binary data without a time period [25,56,57]; median values [18,46,57,59,86]; data in person years [21]; or a 15-year time period [55] [20], with adherence ranges of 22.0-45.1%. Patient adherence rates for individual oral antipsychotics were not extensively characterized in the literature reviewed.…”
Section: Direct Costs Associated With Oral Antipsychotic Treatment Ad...supporting
confidence: 84%
See 1 more Smart Citation
“…When a PDC of 80% or higher was used, adherence was reported to be below 50% (range 9.0-33.2%) in 11 of 12 studies with 6-12 months of follow-up [34,42,[44][45][46][47][48][49][50][51][52] (Table 2). These findings were consistent with adherence rates assessed by MPRs of 80% or higher (Table 2), with oral antipsychotic adherence of less than 50% in 5 of 7 studies over 6-12 months of follow-up [29,45,53,54], and by MPRs of 70% or higher [19,80,81]; for reporting an 18-month time point or only baseline adherence [38,56,77]; for not reporting a time period [76]; and for reporting mean PDC or MPR values only [32,37,65,66] Studies were excluded for reporting binary data without a time period [25,56,57]; median values [18,46,57,59,86]; data in person years [21]; or a 15-year time period [55] [20], with adherence ranges of 22.0-45.1%. Patient adherence rates for individual oral antipsychotics were not extensively characterized in the literature reviewed.…”
Section: Direct Costs Associated With Oral Antipsychotic Treatment Ad...supporting
confidence: 84%
“…In these studies, 9.4-50.9% of patients in the study population took olanzapine [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], 11.5-30.7% took quetiapine [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], 2.0-40.0% took risperidone [18-21, 23, 24, 26-34], 4.0-21.5% took aripiprazole [18-21, 23, 24, 26-32, 35], and 0-7% took clozapine [20, 24-26, 31, 36]. In realworld studies published prior to 2006, olanzapine was the administered treatment for an estimated 16.0-50.9% [18,21,25,27,30,32,33] of patients making up the study population; however, this range dropped to below 20% after 2006 (9.4-17.4%) [20,23,24,26,28,29,…”
Section: Direct Costs Associated With Oral Antipsychotic Treatmentmentioning
confidence: 99%
“…The longer the treatment, the greater the chance of insufficient adherence. Data from administrative claims in the US suggest that, in clinical practice, patients with psychosis treated in an outpatient setting fill their prescriptions an average of 40‐60% of the days prescribed. Adherence studies find that poor mid‐term adherence ranges from 11.6% based on self‐report to 58.4% in studies using serum concentration.…”
Section: Efficacy Effectiveness and Tolerabilitymentioning
confidence: 96%
“…8 So far, there has been limited exploration of how lurasidone fares in clinical practice. One study has reported lower rates of discontinuation with lurasidone compared with other SGAs when measuring health insurance administrative claims, 9 but was unable to determine predictors of treatment continuation.…”
Section: Introductionmentioning
confidence: 99%